2009
DOI: 10.1128/aac.01424-08
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriostatic and Bactericidal Activities of Tigecycline against Coxiella burnetii and Comparison with Those of Six Other Antibiotics

Abstract: The present article is a study of the in vitro susceptibility of eight Greek Coxiella burnetii isolates, derived from patients with acute Q fever, and two reference strains of Coxiella burnetii to tigecycline. The bacteriostatic activity of tigecycline was compared with those of six other antibiotics using a shell vial assay. The MICs of the examined antibiotics were as follows: tigecycline ranged from 0.25 to 0.5 g/ml; doxycycline, trovafloxacin, and ofloxacin ranged from 1 to 2 g/ml; linezolid and clarithrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 21 publications
1
16
0
1
Order By: Relevance
“…39 New generation antibiotics are being applied in clinical trials. 40,41 In some paediatric cases, gamma-interferon is the treatment of choice. 42 The Australian National Vaccination Program was launched in 2001.…”
Section: Treatment and Prophylaxis: Is It Enough?mentioning
confidence: 99%
“…39 New generation antibiotics are being applied in clinical trials. 40,41 In some paediatric cases, gamma-interferon is the treatment of choice. 42 The Australian National Vaccination Program was launched in 2001.…”
Section: Treatment and Prophylaxis: Is It Enough?mentioning
confidence: 99%
“…The second case was successfully treated with intravenous tigecycline, which has not been previously used in this setting to the best of our knowledge. A previous study showed low minimum inhibitory concentration values when tigecycline was tested with Coxiella burnetii strains, although information relating to Rickettsia species is lacking …”
mentioning
confidence: 99%
“…A previous study showed low minimum inhibitory concentration values when tigecycline was tested with Coxiella burnetii strains, although information relating to Rickettsia species is lacking. 1 There are several reports of splenic infarction occurring in the context of a rickettsial infection. A 41-year-old man in Los Angeles with murine typhus (R. typhi) had several splenic infarcts, which necessitated splenectomy.…”
mentioning
confidence: 99%
“…Some authors recommend lifelong treatment in the case of endocarditis [112] since repeated reactivations (relapses) have been observed during treatment interruptions [45]. More recent alternatives for antibiotic treatment include tigecycline and clarithromycin [114]. …”
Section: Recipientsmentioning
confidence: 99%
“…The detection of C. burnetii in cell culture is performed on L929 fibroblasts or other cells such as vero cells [27,114,115]. For analysis, samples are extracted after filtration using 0.45 µm filters.…”
Section: Current Knowledge About the Pathogenmentioning
confidence: 99%